The influence of Leadership Competencies, Organizational Commitment and Job Climate on Organizational citizenship behavior (OCB) and impact Employee Performance at PT Japfa Comfeed Indonesia Tbk. - Musriha Musriha; Siti Rosyafah (Universitas Kadiri, 2022)
This research discusses, the influence of leadership competensies, organizational commitment and job climate on Organizational citizenship behavior and impact employee performance at PT. Japfa Comfeed Indonesia Tbk. The respondent being analyzed are 116 employee at PT. Japfa Comfeed Indonesia Tbk. The tool used for analyzing is the path analysis obtained through the software PPS. To Sum up, the result show that: (1) Leadership competencies no significant effect on Organizational citizenship behavior (OCB); (2) Significantly influence the organizational commitment Organizational citizenship behavior (OCB); (3) Significantly influence the working climate of Organizational citizenship behavior (OCB); (4) Leadership competencies no significant effect on employee performance; (5) Organizational commitment has no significant effect on employee performance; (6) Climate significant effect on employee performance; (7) Organizational citizenship behavior (OCB) significantly affects the performance of employees; (8) The results showed a variable working climate is the dominant influence on Organizational citizenship behavior (OCB) and the performance of employees